The Shifting Landscape in Utilization of Inpatient, Observation, and Emergency Department Services Across Payers. Issue 6 (1st June 2017) - Nuckols, Teryl K.; Fingar, Kathryn R.; Barrett, Marguerite; Steiner, Claudia A.; Stocks, Carol; Owens, Pamela L.
Abstract : Recent policies by public and private payers have increased incentives to reduce hospital admissions. Using data from four states from the Agency for Healthcare Research and Quality Healthcare Cost and Utilization Project, this study compared the payer‐specific population‐based rates of adults using inpatient, observation, and emergency department (ED) services for 10 common medical conditions in 2009 and in 2013. Patients had an expected primary payer of private insurance, Medicare, Medicaid, or no insurance. Across all four payer populations, inpatient admissions declined, and care shifted toward treat‐and‐release observation stays and ED visits. The percentage of hospitalizations that began with an observation stay increased. Implications for quality of care and costs to patients warrant further examination.